Influence of novel microbial formulations on enzymes and microbial indices of soil during wheat cultivation - JAISWAL, PRANITA; SINGH, YUDH VIR; SHARMA, NEHA; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted to study the comparative influence of microbial preparations ,viz. phosphate solubilizing fungi (Jumpstart 2.0), phosphate solubilizing bacteria (PSB), Arbuscular mycorrhiza fungi and humic acid formulation (Bolt GR), in different combinations on soil microbial population and properties (Alkaline phosphatase, dehydrogenase, FDA hydrolytic activity, soil microbial biomass). Bacteria dominated the microbial population, with initial cfu level of 1.73 × 107 to a maximum of 6.2 × 107 gm-1 soil on 90 days after sowing (DAS) in plot, where PSB was applied @ 500 g/ ha, while plots with Jumpstart 2.0 application (@1.65 ml/ kg seed) recorded higher fungal population (7.4 × 106 cfu/g). Treatments and crop age had significant impact on microbial population and their interaction was also found to be significant. Soil microbial properties also increased significantly with crop aging and reached to a higher level on 90 DAS for all the treatments. Microbial activity was invariably found to be highest in T7 treatment (application of PSF @ 0.83 ml/kg seed with humic acid @ 10 kg/ha), and lowest in control plots irrespective of sampling intervals. Results concluded that application of PSF, PSB, AM Fungi and organic formulations in different combination had favourably influenced the microbial properties of soil.